Changes in Tolaki People Burial in Southeast Sulawesi: From Boat-Shaped Grave Coffin (Soronga) to Boat-Shaped Islamic Tomb (Koburu Bangga) - Syahrun Syahrun; Basrin Melamba (Department of History, Faculty of Humanities, Diponegoro University, 2022)
The first burial system of Tolaki people in prehistoric times and ancient times adopted boat-shaped grave coffin known as soronga or oduni. There were large and small soronga and there were also decorated and undecorated or plain soronga. When Islam was introduced in the Mekongga Kingdom during the leadership of King/Bokeo Laduma in 17th century and in Konawe in 18th century, the burial system was adopted. However, the tradition of using boats experienced a change. During the Islamic era, there were two shapes of grave in the Islamic grave called as ninggeo-nggeo where the grave was placed in a hole made on the side of the excavation and tinandapa where the grave was placed in a hole made in the middle of the excavation and it was intended for elite and influential ruler. There were also four models of tomb types, namely circle (buboto/loelole), rectangular (konahuu), rectangular step pyramid, elongated (menda’a), and boat-shaped (obangga). koburu bangga tomb. The distribution pattern of the tombs varied, there were converging (metobu), circular, and spreading patterns. The shape of tombstone also varied, it resembled pappilus genital, round stone, wide wood and stone, human head, knights grinding stone (oliro). It was made of stone, river stone, mountain stone, wood, and even tree was also used as a tomb marker. The boat-typed tomb still maintained because a faith that the deceased need vehicles to go to their destination. It is also affected by maritime world at the past as well as technology that lived in the past used by a collective memory.